Selection of constructive systems using BIM and multicriteria decision-making method - Machado, Eduarda Lauck; Sotsek, Nicolle Christine; Scheer, Sergio; Santos, Adriana de Paula Lacerda (Revista ALCONPAT, 2018)
The objective of this study is to identify if the use of a BIM platform software associated to AHP decision-making method can assist in the decision making process during the project design phase. Three construction systems are analyzed: Structural Masonry, Light Steel Framing and Light Wood Framing. The BIM modeling enabled scenario simulations and facilitated the extraction of data, which, in turn, assisted the specialists in the selection of the most appropriate constructive system, considering the established criteria. The originality of this research is to consider several factors relevant to the choice of the constructive system, and its limitation is in the modeling only of the walls of the analyzed constructive systems, and not of the complete building.